Orthoseira groenlandica sp. nov., a new aerophilic diatom (Orthoseirales, Bacillariophyta) species from Greenland - Goeyers, Charlotte; Kochman-Kędziora, Natalia; van De Vijver, Bart (Phytotaxa, 2023)
During the survey of the moss-inhabiting diatoms in samples from Greenland, an unknown Orthoseira taxon was observed that was originally identified as O. roeseana but differed from the recently published lectotype population of the latter. Comparison with all known Orthoseira taxa worldwide showed that the unknown taxon represented a new species that is described as O. groenlandica, sp. nov. based on detailed light and scanning electron microscopy. The combination of the unique, rather chaotic valve face and mantle surface ornamentation, the absence of caverns and marginal pore fields, the presence of robust, short spines, and the absence of chain-like colonies has not been observed so far in any known Orthoseira species. The morphology of the new species is discussed comparing it with the morphology of all other Orthoseira species worldwide by carefully analysing the different morphological features observed so far in members of the genus Orthoseira. Brief notes on the ecology of the sample where the new species was found are added.